Pendidikan Berbasis Manajemen Bisnis - Ach. Syaiful; Hafid; Musayyidi (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2024)
The reformulation of Indonesia’s education system is essential to enable it to respond to global challenges, particularly within the context of a technology-based economy. Education can no longer merely address social and individual needs; it must also adapt to the demands of the global market. The concept of Management Business Education (MBE) is proposed as a strategic approach to align education with global needs without abandoning local values. In this model, education is directed toward systematically developing students’ potential, equipping them with business and management insights, and strengthening collaboration among educational institutions, parents, and the market environment. In this way, education can serve as a vital instrument in shaping a generation that is adaptive, innovative, and highly competitive in the era of globalization.